Pengaruh Prinsip-Prinsip Good Corporate Governance Terhadap Kinerja Keuangan Lembaga Perkreditan Desa (LPD) di Kota Denpasar - Mahaendrayasa, Putu Krishna Araytsha; Dwija Putri, Gusti Ayu Made Asri (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p04, 2017)
Good Corporate Governance is a corporate governance that explains the relationship between all stakeholders in organized and organized business. Principles of Good Corporate Governance need to be applied by LPDs, as they can reduce agency conflict between LPD owners and LPD Managers, thus increasing the performance of LPDs. Corporate Governance contains the concept of separation between ownership and control of the company. Company managers are authorized to run the company and make decisions on behalf of the owner. With information owned, managers can act only to benefit themselves by sacrificing the interests of the owner, so that the information conveyed to the owner is not in accordance with the actual company conditions. The success of LPD can be seen from LPD health level. This study aims to determine the influence of Good Corporate Governance principles (transparency, accountability, responsibility, independency, and fairness) on the financial performance of Lembaga Perkreditan Desa (LPD) in Denpasar City. The number of samples used in this study were 35 LPDs with 70 respondents. Determination of sample using nonprobability sampling method with saturated sample technique. Analytical technique used is multiple linear regression, and previously done instrument testing and classical assumption test for the accuracy of regression analysis results. Based on the result of hypothesis pengujiam known that the principles of Good Corporate Governance: accountability, independency, and fairness have positive and significant influence, while transparency and responsibility have positive and insignificant effect on financial performance of LPD in Denpasar City.
Keywords: transparency, accountability, responsibility, independency, fairness, Performance, Finance